2022
DOI: 10.1159/000523735
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Sentinel Lymph Node Biopsy by Vaginally Assisted Natural Orifices Endoscopic Transluminal Endoscopic Surgery in Early Stage Endometrial Cancer: Description of Technique and Surgeon’s Perspectives after the First Experience

Abstract: Endometrial cancer is the most commonly diagnosed gynecological malignancy. Feasibility and safety of laparoscopy are no longer to be demonstrated in patients with uterine-confined endometrial carcinoma. Vaginally assisted natural orifices endoscopic transluminal endoscopic surgery (vNOTES) is a new endoscopic approach over the past decade with significant evidence in benign pathology. Publications exploring VNOTES surgery in gynecological cancer were published first in 2014. We hereby report our first experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We proposed a standardized 10-step approach for SLN mapping by retroperitoneal vNOTES for patients with early-stage endometrial and cervical cancer. Since Baekelandt first described this technique in 2019 [ 12 ], only a few articles have been published on this topic, including case reports, small single-center case series, and proposals for technique modifications [ 14 , 15 , 16 , 17 , 18 , 19 , 22 ]. Following the IDEAL (Idea Development Exploration Assessment Long-term follow-up) framework, we can consider that research regarding this technique is in Stage 2a (Development), and its standardized description appeared necessary before moving to Stage 2b (Exploration), allowing for a greater surgical homogeneity required to conduct larger multi-center studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We proposed a standardized 10-step approach for SLN mapping by retroperitoneal vNOTES for patients with early-stage endometrial and cervical cancer. Since Baekelandt first described this technique in 2019 [ 12 ], only a few articles have been published on this topic, including case reports, small single-center case series, and proposals for technique modifications [ 14 , 15 , 16 , 17 , 18 , 19 , 22 ]. Following the IDEAL (Idea Development Exploration Assessment Long-term follow-up) framework, we can consider that research regarding this technique is in Stage 2a (Development), and its standardized description appeared necessary before moving to Stage 2b (Exploration), allowing for a greater surgical homogeneity required to conduct larger multi-center studies.…”
Section: Discussionmentioning
confidence: 99%
“…The retroperitoneal vNOTES approach appears to be the most promising, providing easy visualization of lymphatic afferent vessels and pelvic lymph nodes (LNs), early LN assessment, and a coherent mapping methodology following the lymphatic flow from caudal to cranial [ 14 ]. Although this technique appears to be a possible revolutionary tool to stage endometrial and cervical cancer, only a few publications have reported it [ 12 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We proposed a standardized 10-step approach for SLN mapping by retroperitoneal vNOTES for patients with early-stage endometrial and cervical cancer. Since Baekelandt first described this technique in 2019 [6], only a few articles have been published on this topic, including case reports, small single-center case series, and proposals for technique modifications [8][9][10][11][12][13]16]. Following the IDEAL (Idea Development Exploration Assessment Long-term follow-up) framework, we can consider that research regarding this technique is at stage 2a (Development), and its standardized description appeared necessary before moving to stage 2b (Exploration), allowing a greater surgical homogeneity required to conduct larger multi-center studies.…”
Section: Discussionmentioning
confidence: 99%
“…The retroperitoneal vNOTES approach appears the most promising, providing easy visualization of lymphatic afferent vessels and pelvic lymph nodes (LNs), early LNs assessment, and a coherent mapping methodology following the lymphatic flow from caudal to cranial [8]. Although this technique appears to be a possible revolutionary tool to stage endometrial and cervical cancer, only a few publications have reported it [6,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, leakage may also occur when the lymphatic vessels are cutoff to create a retroperitoneal space, and substantial damage can occur when the lateral bladder space is opened. The relevant studies at present are case reports or small sample size retrospective studies 7 , 9 , 23 ; therefore, the retroperitoneal approach needs further evaluation.…”
Section: Discussionmentioning
confidence: 99%